CONSTRUCTIVE CONSTRUCTION-TECTONICS OF HISTORICAL MONUMENTS (Academia Science Repository, 2023)
In the article, the constructions used in the restoration of buildings are studied; the physical-mechanical properties of the constructions, their importance in ensuring durability are studied. In addition, in the historical monuments of Uzbekistan, the appearance of the dome constructions of the upper part of the building, the diameter of the outer dome and the materials are indicated. In historical buildings, the characteristic features such as the expansion of vaulted rooms, their efficient use and the creation of convenient opportunities for making the interior more beautiful have been revealed.